A panel method for floating offshore wind turbine simulations with fully integrated aero- and hydrodynamic modelling in time domain. Issue 3 (2nd September 2018) - Netzband, Stefan; Schulz, Christian W.; Göttsche, Ulf; Ferreira González, Daniel; Abdel-Maksoud, Moustafa
ABSTRACT: The further development of the first-order panel method pan MARE for simulating floating offshore wind turbines (FOWTs) in time domain is presented in this work. Based on a surface discretisation of platform, tower and rotor with its wake, the three-dimensional aerodynamic and hydrodynamic flow fields are calculated. A free wake deformation model is integrated to capture blade–wake interaction. Hydrodynamic, aerodynamic and mooring loads are cumulated by a six-degrees-of-freedom solver to compute the motion of the FOWT. The presented method is able to simulate unsteady and aperiodic motions and to predict the wake deformations and their influence on the rotor loads due to the platform motion. In order to verify the method, simulation results of the DeepCWind floater with the NREL 5-MW baseline turbine are compared with those obtained in the OC4 project. The ability to capture highly unsteady situations is studied as well by simulating a gust with varying length.